Rewilding of Protected Areas Enhances Resilience of Marine Ecosystems to Extreme Climatic Events - Sheehan, E. V.; Holmes, L. A.; Davies, B. F. R.; Cartwright, A.; Rees, A.; Attrill, M. J. (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are employed as tools to manage human impacts, especially fishing pressure. By excluding the most destructive activities MPAs can rewild degraded areas of seabed habitat. The potential for MPAs to increase ecosystem resilience from storms is, however, not understood, nor how such events impact seabed habitats. Extreme storm disturbance impact was studied in Lyme Bay MPA, Southwest United Kingdom, where the 2008 exclusion of bottom-towed fishing from the whole site allowed recovery of degraded temperate reef assemblages to a more complex community. Severe storm impacts in 2013–2014 resulted in major damage to the seabed so that assemblages in the MPA were more similar to sites where fishing continued than at any point since the designation of the MPA; the communities were not dominated by species resistant to physical disturbance. Nevertheless, annual surveys since 2014 have demonstrated that the initial recovery of MPA assemblages was much quicker than that seen following the cessation of chronic towed fishing impact in 2008. Likewise, General Additive Mixed Effect Models (GAMMs) showed that inside the MPA increases in diversity metrics post-Storm were greater and more consistent over time than post-Bottom-Towed Fishing. As extreme events are likely to become more common with climate change, wave exposure observations indicated that 29% of coastal reef MPAs around the United Kingdom may be exposed to comparable wave climate extremes, and may be similarly impacted. This paper therefore provides an insight into the likely extent and magnitude of ecological responses of seabed ecosystems to future extreme disturbance events.